Surveillance on swine farms using antemortem specimens - Munguía-Ramírez, Berenice (Burleigh Dodds Series in Agricultural Science, 2023)
In the recent past, disease control on swine farms was based on vaccination or intentional exposure to pathogens to stimulate immunity and protect against clinical disease. This one-dimensional strategy became increasingly inadequate as farms increased in size and as pathogens resistant to immune control became commonplace, e.g. porcine reproductive and respiratory syndrome virus (PRRSV) and others. Today, prevention and control requires the coordinated use of (1) immunity to reduce clinical losses, (2) biosecurity to stop the entry of pathogens, and (3) surveillance to verify that immunity and biosecurity strategies are functioning properly. Of the three, surveillance has been the most difficult to implement, both because populations on swine farms are complex and because practical surveillance methods have only become available in recent years. Herein we outline the elements of designing and implementing infectious disease surveillance in commercial swine herds using diagnostic testing of antemortem samples.